Role of transabdominal ultrasound in detection of ectopic pregnancy - Thapa, Narayan Bikram; Dwa, Yam Prasad (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Ectopic pregnancy is one of the common medical emergencies encountered in the clinical practice. Confirmation of diagnosis is usually done by urine pregnancy test and transabdominal sonography. Thus, the present study is carried out to determine the role of transabdominal ultrasonography in the diagnosis of ectopic pregnancy by comparing the ultrasonography findings with that of operative and histopathology and to evaluate clinical profile of the women with confirmed ectopic pregnancy. Materials & Methods: Transabdominal ultrasound record of patients referred for first trimester ultrasound, from January 2008 to December 2015, at radiology department of Kist medial college teaching hospital were reviewed to identify patients with ectopic pregnancy. Among these patients those who underwent surgery and histopathology confirmed ectopic pregnancies were identified and their medical records were retrieved. Ultrasound and clinical profile were recorded and statistically analyzed. Results: There were 19 patients with ultrasound diagnosis of ectopic pregnancy among 1480 first trimester ultrasound record. Among these patients, ectopic pregnancy was confirmed on 18 patients. Ultrasound diagnosis included adnexal mass with pelvic fluid in 15 (83.3%) patients and pelvic fluid without adnexal mass in 4 (16.7%) patients. The study result revealed that sensitivity of transabdominal ultrasonography was 100% and specificity was 99.9%. Positive predictive value and negative predictive value of transabdominal ultrasonography was 94% and 100%. Conclusion: The transabdominal ultrasound accurately diagnose ruptured ectopic pregnancy. JCMS Nepal. 2016;12(1):1-4.